Effectiveness of Material Compliance Supervision to Improve Tax Compliance at The Cirebon Satu Primary Tax Service Office - Andi Alimudin Zaen; Moh Taufik Hidayat; Ipik Permana (International Journal of Business, Economics, and Social Development, 2026)
Tax revenue plays a vital role in supporting national development, particularly in countries implementing a self-assessment tax system such as Indonesia. Under this system, effective tax oversight is crucial to ensure taxpayer compliance, particularly material compliance, which relates to the substantive accuracy of tax reporting. This study aims to analyze the effectiveness of Material Compliance Oversight (PKM) in improving taxpayer compliance at the Cirebon Satu Primary Tax Service Office (KPP Pratama Cirebon Satu) and to identify factors influencing its implementation. This study adopted a descriptive qualitative approach. Data were collected through in-depth interviews with Public Accountant Representatives, supervisory officials, and tax consultants, supported by direct observation and documentation analysis. Data were analyzed using qualitative analysis stages, including data reduction, data presentation, and conclusion drawing, with triangulation techniques applied to ensure data validity. The results indicate that Material Compliance Oversight has contributed to improving taxpayer compliance, although its effectiveness remains at a moderate level. Economic deterrence, particularly through administrative sanctions and perceived tax audit risk, was found to be the most influential factors in driving compliance. Conversely, normative motivation alone did not consistently lead to higher material compliance. Taxpayers' perceptions of the tax system, including administrative simplicity, service quality, and legal certainty, positively influence the acceptance of supervision results. Perceptions of fairness and equality strengthen the legitimacy of supervisory actions and encourage cooperative compliance behavior. Factors supporting the effectiveness of PKM include data- and risk-based supervision, increased digitalization of tax administration, and enhanced human resource competency. However, limited data quality, variations in communication skills among supervisors, taxpayer financial constraints, and frequent changes in performance indicators were identified as inhibiting factors. This study concludes that optimizing Material Compliance Supervision requires strengthening data quality, enhancing supervisory competency, and integrating law enforcement with educational and service-oriented approaches to support sustainable taxpayer compliance and state revenue performance. Keywords: Material compliance supervision, tax compliance, account representative, tax administration, taxpayer behavior